Implementasi Peraturan Daerah Nomor 6 Tahun 2013 Tentang Pengelolaan Zakat Terkait Upaya Pengentasan Kemiskinan untuk Mewujudkan Kesejahteraan Masyarakat dan Keadilan Sosial di Kabupaten Siak - Indra, Mexsasai; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The problem of poverty in the community remains a major problem facedby the Indonesian people. Of course, various efforts have been made by thegovernment, but have not shown satisfactory results. Likewise with the SiakDistrict Government where in the Regional Regulation of Siak Regency No. 6 of2013 on the Management of Zakat also disputes as addressing the problem ofpoverty. Zakat itself as a mandatory worship of Muslims, as well as the economicequity in a country. Therefore, the introduction of the zakat mechanism is neededas an alternative approach to solving the problem of poverty.Government based on Presidential Decree Number 8 Year 2001establishes National Amil Zakat Body or abbreviated BAZNas is the only officialzakat amil institution which has the task of collecting and distributing zakat, infak,and alms (ZIS) at national level. The purpose of the establishment of BAZNas isfor zakat to be well managed, centralized, and right on target. The performance ofBAZNas should be evaluated whether or not the agency is in poverty alleviation.BAZNas has a variety of programs that are expected to provide a solution toreduce poverty in Indonesia, so the government to hold BAZNas in every regionand region.This research is in the form of field research by looking at correlationbetween Regional Regulation of Siak Regency Number 6 Year 2013 AboutManagement of Zakat with Amil Zakat Agency of Nasiolal of Siak Regency asthe driving force of the Regional Regulation in zakat management, with the objectof research is the problem of poverty in Siak District. The results of this studyshow the role of BAZNas in running the Regional Regulation in povertyalleviation does exist, but not yet significant. In realization, the programowned by BAZNas can be said passive. The BAZNas program is not wellimplemented due to lack of personnel and government attention. YetBAZNas is an amil zakat institution established by the government itself asthe management of zakat for poverty alleviation.Keywords: Zakat Management, Poverty Reduction, Community Welfare